Comparison of LEACH and PEGASIS Hierarchical Routing Protocols in WSN - El Ouadi, Mohammed Réda; Hasbi, Abderrahim (International Journal of Online and Biomedical Engineering (iJOE), 2020)
Wireless Sensor Networks is a group of sensor nodes dispatched in a geographical area for a defined objective. These sensor nodes are characterized by limited capacity of communicating, computing and especially of energy. The performance of these WSN is resting on a good routing protocol, hence the need to choose the routing protocol able to satisfy the wsn’s objectives, and to satisfy the common challenge to prolong network life time. Several routing concepts have been proposed for the WSN, hierarchical routing is one of the most used concepts. It is divided into 3 types: cluster based routing, grid based routing and chain based protocol. In this paper, we are interested to Study, analyse and compare two popular routing protocols for Wireless sensor networks (WSNs), Low-Energy Adaptive Clustering Hierarchy (LEACH) using clusters based concept and Power-Efficient Gathering in Sensor Information System (PEGASIS) with chain based concept. The both protocols are simulated with Matlab simulator, in order to evaluate its performances against the different users and the WSNs objectives defined.